Negative Word of Mouth On Social Media: A Case Study of Deutsche Bahn’s Accountability Management - Mirbabaie, Milad; Stieglitz, Stefan; Marx, Julian (Schmalenbach Journal of Business Research)
Abstract The advent of social media and its commodification have created a never-ending feedback loop between businesses and their customers. In this context, constant negative Word-of-Mouth (NWOM) may jeopardize a corporate image and cause defensiveness in corporate communication. This paper presents a case study of several customer service accounts of the railway company Deutsche Bahn on Twitter to investigate the management and control of constant NWOM and the impact of accountability strategies on customers’ perception of the firm. To this end, a sample of 36,757 Twitter postings was drawn and analyzed by means of sentiment and content analysis techniques. The findings suggest that the perceived accountability towards the firm declined in case of an attitude shift towards the user. In contrast, the firm was being held accountable more insistently after expressed defensiveness, regardless of the firm’s actual accountableness. With this paper, we introduce the notion of accountability management and an accompanying theoretical framework to the literature. This provides a novel perspective on constant NWOM countermeasures for organizations that are part of ‘toxic’ industries or face unrightfully claimed accusations, i.e., when being held accountable for outer circumstances beyond their control.
Keywords: Management of Technology and Innovation; General Economics; Econometrics and Finance; General Business; Management and Accounting

Improved output gap estimates and forecasts using a local linear regression - Fritz, Marlon (International Economics)
Keywords: General Economics; Econometrics and Finance; General Business; Management and Accounting

Citizen Social Science in Germany—cooperation beyond invited and uninvited participation - Göbel, Claudia; Mauermeister, Sylvi; Henke, Justus (Humanities and Social Sciences Communications)
Abstract This article presents an overview of characteristics of Citizen Social Science (CSS) in Germany. CSS is defined as scientific research in the humanities and social sciences, carried out in cooperation between professional and non-professional researchers. The study draws on an online survey and semi-structured interviews with project coordinators and co-researchers. It finds that participatory research activities in the humanities and social sciences are very diverse in their disciplinary traditions and organisational settings. Key features of CSS activities initiated inside as well as outside academic institutions are analysed to understand patterns of participation and cooperation. The results show that CSS activities are frequently realised in heterogeneous consortia of academic and non-academic partners. These consortia influence interactions between professional and non-professional researchers. To investigate these observations further, the article extends the analytical gaze from participation of individual volunteers to various forms of cooperation in consortia. This shift in attention brings to sight additional actors and activities that are usually not, or only marginally, considered in discussions about C(S)S. Staff of civil society organisations, municipalities, schools or cross-sectoral initiatives as well as university students are involved in making CSS work. In addition to research tasks, CSS rests on science communication, project management and intermediation activities. This extended perspective captures more diverse constellations of knowledge production in participatory research in the social sciences and humanities than the common focus on participation. In this way, the article aims to lay the groundwork for understanding the functioning of CSS beyond aspects described by the concept of invited and uninvited participation. It shows that CSS activities are not limited to capacitating lay people for participation in science. A more adequate description is that such projects are concerned with facilitating cooperation with co-researchers and other partners in consortia inside and outside of academia. On this basis, the article introduces the notion of cooperation capacity as a heuristic device to propose new prompts for research on CSS as well as for supporting CSS practice.
Keywords: General Economics; Econometrics and Finance; General Psychology; General Social Sciences; General Arts and Humanities; General Business; Management and Accounting

Narratives in entrepreneurial ecosystems: drivers of effectuation versus causation - Hubner-Benz, Sylvia; Most, Fabian; Wirtz, Jochen; Auer, Christine (Small Business Economics)
This paper introduces narratives in entrepreneurial ecosystems as drivers of effectuation vs. causation. Drawing on 43 interviews with successful players in Silicon Valley, Munich, and Singapore, we found ecosystem-specific narratives indicate what is common, appropriate, and successful in each ecosystem, and these narratives encourage either effectuation or causation. Our findings indicate that the narratives in the ecosystem in Silicon Valley facilitate effectuation, in Munich causation, and in Singapore a cautious balance of both. Our research suggests that narratives can explain mechanisms how ecosystems influence entrepreneurship: the national culture, market characteristics, available resources, and networks in an ecosystem spark ecosystem-specific narratives, which in turn shape tendencies towards effectuation and causation. Thereby, we introduce a new ecosystem-focused perspective on predictors of effectuation and causation.
Keywords: Economics and Econometrics; General Business; Management and Accounting

From entrepreneurial experience to expertise: A self-regulated learning perspective - Winkler, Christoph; Fust, Alexander; Jenert, Tobias (Journal of Small Business Management)
Keywords: Management of Technology and Innovation; Strategy and Management; General Business; Management and Accounting

The Legacy of Gurus: The Impact of Armin Diel and Joel Payne on Winery Ratings in Germany - Frick, Bernd (Journal of Wine Economics)
Abstract Changes in winery ratings in leading wine guides, that is, improvements as well as deteriorations, are typically attributed to corresponding changes in the quality of the wines produced by the respective winery. What remains unexplored in this context is changes in editorship and/or changes in the composition of the wine tasting teams working for the respective guide. Using data from two particularly prestigious German wine guides (Gault Millau and Vinum), this paper shows that these latter changes have a rather small, yet statistically significant impact on changes in winery ratings. Thus, consumers are well-advised to consider these changes before making their purchasing decision. (JEL Classifications: L21, M30, Q13)
Keywords: Horticulture; General Business; Management and Accounting; Food Science

Machine learning and natural language processing on the patent corpus: Data, tools, and new measures - Balsmeier, Benjamin; Assaf, Mohamad; Chesebro, Tyler; Fierro, Gabe; Johnson, Kevin; Johnson, Scott; Li, Guan‐Cheng; Lück, Sonja; O'Reagan, Doug; Yeh, Bill; Zang, Guangzheng; Fleming, Lee (Journal of Economics & Management Strategy)
Drawing upon recent advances in machine learning and natural language processing, we introduce new tools that automatically ingest, parse, disambiguate, and build an updated database using U.S. patent data. The tools identify unique inventor, assignee, and location entities mentioned on each granted U.S. patent from 1976 to 2016. We describe data flow, algorithms, user interfaces, descriptive statistics, and a novelty measure based on the first appearance of a word in the patent corpus. We illustrate an automated coinventor network mapping tool and visualize trends in patenting over the last 40 years.
Keywords: Management of Technology and Innovation; Strategy and Management; Economics and Econometrics; General Business; Management and Accounting; General Medicine